Acumulação e translocação de elementos vestigiais em Cistus ladanifer L. de áreas mineiras da FPI portuguesa - Abreu, M.M. (2011)
The accumulation and translocation of As, Cu, Pb and Zn in different Cistus ladanifer L. populations colonizing mine areas of Brancanes, Sao Domingos, Chanca and Caveira (Portuguese Iberian Pyrite Belt) and two control areas (Caldeirao and Pomarao) was evaluated. Soils from Sao Domingos and Caveira presented the greatest total concentrations of As, Cu and Pb. Brancanes and Chanca mine areas might be considered in natural attenuation processes relatively to the past mining activity that cessed about one century ago. Plants are, except those from Caveira mine area, Zn accumulators. The concentration of Pb in plants (aerial part) from the control and Sao Domingos areas are within the range considered phytotoxic. Trace elements concentrations in plants are below the domestic animal toxicity limits. Cistus ladanifer might be used in phytostabilization programs of other mine areas as trace elements concentrations in soils did not influence the behaviour of the different plant populations